I finanziamenti ad alta tecnologia: una sfida concettuale (Milan Law Review, 2020)
Business financing operations are now hit by the wave of innovation brought by digital technologies. We are not faced only with process innovations (= in the production processes of the economic-legal affair), but, more radically, with content, that is the production of intrinsically original events. The plans on which this interaction takes place are many: the object of the loan (the type of resource transferred), the financial relationship (the nature of the legal position signed), the size of the subjects and the dynamics of their contact. The advent of applications and digital connections, at each of these levels, is challenging and the challenge is not focused only on the reconstruction of the discipline from a technical point of view, but first of all affects the conceptual categories on which it is based; the paper is dedicated to the consideration of the implications that arise under the latter profile.
Keywords: New technologies – business financing – Cryptocurrencies – Blockchain – Token